What Has IoT Got to Do with HR and People: A Case of Delloitte - Saurabh Anand, Ila Mehrotra Anand, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Interacting with software using keyboard and mouse will soon be history. Voice, speeches, gestures are the next big thing in communication. IoT will certainly produce a large amount of people-related data and it is this data that is going to be really useful for decision taking purposes. HR would need to incorporate technology to successfully control the organizational human resources. IoT will allow us to access our data and other applications like Continuous Performance Management, where digital culture is required to create a genuinely valuable connection between an employee and his or her staff. It also helps to exchange thoughts and experiences through social media collaboration which is a driving force for all employees. The paper tries to analyze the role of IoT in People analytics, challenges associated with it and how Delloitte Canada has gone about implementing it across their organization.